Shades of Earth - Revis, Beth. (New York, N.Y. : Razorbill, an imprint of Penguin Group (USA), 2013)
"When young lovers Amy and Elder and the other passengers of the spaceship Godspeed finally land on Centauri-Earth and start to colonize the new world, they encounter pterodactyl-like monsters and the threat of unseen aliens"--Provided by publisher.
Booklist, December 2012
Horn Book, January 2013
Kirkus Review, December 2012
Young Adult
Young Adult.
Booklist
Keywords: Space colonies -- Juvenile fiction; Survival -- Juvenile fiction; Space colonies -- Fiction; Survival -- Fiction; Love -- Fiction; Science fiction; Space colonies -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Love stories; Science fiction; Love stories; Science fiction